PENGEMBANGAN MODUL DIGITAL BERBASIS NILAI KEPAHLAWANAN GUSTI KETUT JELANTIK UNTUK MENUNJANG MOTIVASI BELAJAR DAN HASIL BELAJAR PESERTA DIDIK KELAS 11 IPS DI SMAN 2 BUSUNGBIU - Nurul Hidayat; Joko Sayono; Aditya Nugroho Widiadi (Universitas Negeri Malang, 2023)
This article is written developed with the first objective, produce digital modules based on I Gusti Ketut Jelantik's heroic values to support motivation and lerning outcomes at SMAN 2 Busungbiu. Second, testing effectiveness of digital module products for support motivation and learning outcomes in class 11 IPS at SMAN 2 Busungbiu. TIn this research useding development model ADDIE (Analyze, Design, Development, Implementation, Evaluation). Subjects experiment in this research is 11 IPS 1 as control class and 11 IPS 2 as experimental class. Material developed use Kurikulum 2013 with Subject History in KD 3.2. for 11th grade. Digital modules that have been developed and tested show data on improvements in learning motivation and learning outcomes. increased motivation using digital modules reached 85.5 percent6% with the criteria of